Increasing Productivity Of Traditional Health Drink - Wike Agustin Prima Dania (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACTThe purposeofthis activityis to applymechanical machine such as washing machine for rhizome (empon-empon), gra-termachine, andhydraulicpress toimpro-ve theperformanceandefficiency of productionprocess oftraditional drinks (jamu). This activity has been done by “learning by doing” method emphasized to practical aspect rather than theoretical aspect. Therefore, there are several activi-ties such as: (1) SurveytoSMEsinBatutraditionaldrinks, namelySMEs